Criminal Liability of Children as Perpetrators of Physical Violence - Maharani, Puan; Sunariyo, Sunariyo (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
Cases of child abuse are increasingly in the public spotlight. In some cases, children can also be perpetrators of violence against other individuals. This phenomenon raises various questions related to legal responsibility, justice approaches, and appropriate treatment of children as perpetrators of criminal acts. This study aims to analyze the criminal responsibility of children as perpetrators of violence and how the Judge's considerations in sentencing in Decision Number 5 / Pid.Sus-Anak / 2022 / PN.Smr and Decision 10 / Pid.Sus-Anak / 2023 / PN.Bpp. This study uses a normative legal research method, with three data sources, namely primary, secondary, and tertiary. Data were obtained through literature study collection techniques, and a legislative approach method with qualitative descriptive analysis, and drawing conclusions using inductive and deductive methods. The results of this study indicate that both Decisions have considered the legal, social, and psychological aspects of children as perpetrators of criminal acts. However, there are several things that are not in line with the principles of child protection and the restorative justice approach mandated by the Child Criminal Justice System Law.